ALLANITE-(Nd) FROM SAPFIRINOVAYA PIT, SOUTHERN URALS: FIRST FIND IN RUSSIA - A.V. Kasatkin; R. Škoda; A.M. Kuznetsov (Минералогия)
Allanite-(Nd) (Ca1.20Mn0.02Nd0.33Ce0.21Sm0.07Pr0.06La0.03Gd0.02Y0.01)Σ1.95(Al1.94Fe2+ 0.46Fe3+ 0.42Mg0.08Sc0 .06Ti0.01)Σ2.97[Si2 O7 ][SiO4 ]O(OH) was found first in Russia as black crystals and grains up to 0.12 mm in size in a sapphirine-bearing rock of the Sapfirinovaya pit, near settlement of Tayginka in Kyshtym area of Chelyabinsk district, Southern Urals. According to strong bands of Raman spectrum of allanite-(Nd) (106, 205, 283, 321, 385, 444, 495, 568, 688, 874, 970, 1051 cm-1), it belongs to the allanite group of the epidote supergroup. Allanite-(Nd) is associated with davidite-(Се) and monazite-(Nd) (first finds in Southern Urals).